Stock market equity advisory tool by using of neural network method - Ng, Shun Yi (2024)
This field of study of this project is a stock market equity advisory tool that will analyze the stock market using machine learning which is Neural Network Method. Stock market prediction like traditional statistical as well as artificial intelligence techniques are used widely in the world. In this study, we proposed a stock market equity advisory tool to analyze Malaysia’s stock market by using the Neural Network Method as the analyzing tool. Malayan Banking Berhad are chosen to be the stock that use to train the model. The historical data of the stock have been getting from yahoo finance and put into the model to do training and testing. After the training, the pre-trained model has been saved and merge to the webpage. A webpage will be deployed to let user to use the tool to do real-time prediction for any stocks in Malaysia. User can choose to predict and get investment recommendation for the next day closing prices or predict for the next five days prices.